ANALISIS PEMANFAATAN TEKNOLOGI DIGITAL SEBAGAI MEDIA PEMBELAJARAN PADA MATA PELAJARAN AL-QUR’AN HADIS - Nurlaili; Suradi, Ahmad; Ai Siti Hodijah; Rafika Dewi Septia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid advancement of digital technology requires education to integrate digital technology into learning, one of which is learning Al-Qur'an Hadith. The learning process requires many components, one of which is learning media, in integrating digital technology into education, educators can do so by using learning media with digital technology. The purpose of this research is to analyze digital technology that can be used in the learning process of Al-Qur'an Hadith and examples of its application. The research method used in this research is the literature method with books, journals, and web articles as sources of information. The results of this study are many digital technologies that can be used by educators in the subject of Al-Qur'an Hadith, including: 1) multimedia learning media which can be in the form of powerpoint, puzzle games and so on, 2) the Internet which can be youtube, web pages and so on, and 3) digital Al-Qur'an, one of which is the Indonesian Al-Qur'an application.